Circulating tumour DNA biomarkers in savolitinib-treated patients with non-small cell lung cancer harbouring MET exon 14 skipping alterations: a post hoc analysis of a pivotal phase 2 study. (October 2022) - Yu, Yongfeng; Ren, Yongxin; Fang, Jian; Cao, Lejie; Liang, Zongan; Guo, Qisen; Han, Sen; Ji, Zimei; Wang, Ye; Sun, Yulan; Chen, Yuan; Li, Xingya; et al.
Background: Savolitinib, a selective MET inhibitor, showed efficacy in patients with non-small cell lung cancer (NSCLC), including pulmonary sarcomatoid carcinoma (PSC), harbouring MET exon 14 skipping alteration ( MET ex14). Objective: To analyse post hoc, the association between circulating tumour DNA (ctDNA) biomarkers and clinical outcomes, including resistance, with savolitinib. Design: A multicentre, single-arm, open-label phase 2 study. Methods: All enrolled patients with baseline plasma samples were included. Outcomes were objective response rate (ORR), progression-free survival (PFS) and overall survival (OS) by baseline MET ex14 and post-treatment clearance, coexisting gene alterations at baseline and disease progression. Results: Among 66 patients with baseline ctDNA sequencing, 46 (70%) had detectable MET ex14. Frequent coexisting baseline gene alterations included TP53 and POT1 mutations. Patients with detectable baseline MET ex14 exhibited worse PFS [hazard ratio (HR), 1.77; 95% confidence interval (CI), 0.88–3.57; p = 0.108] and OS (HR, 3.26; 95% CI, 1.35–7.89; p = 0.006) than those without, despite showing a numerically higher ORR. Among 24 patients with baseline detectable MET ex14 and evaluable postbaseline samples, 13 achieved MET ex14 clearance post-treatment. Median time to first clearance was 1.3 months (range, 0.7–1.5). MET ex14 post-treatment clearance was associated with better ORR (92.3%; 95% CI, 64.0–99.8 versus 36.4%; 95% CI, 10.9–69.2; p = 0.0078), PFS (HR, 0.44; 95% CI, 0.2–1.3; p = 0.1225) and OS (HR, 0.31; 95% CI, 0.1–1.0; p = 0.0397) versus non-clearance. Among 22 patients with disease progression, 10 acquired pathway alterations (e.g. in RAS/RAF and PI3K/PTEN) alone or with secondary MET mutations (D1228H/N and Y1230C/H/S). Conclusion: ctDNA biomarkers may allow for longitudinal monitoring of clinical outcomes with savolitinib in patients with MET ex14-positive PSC and other NSCLC subtypes. Specifically, undetectable baseline MET ex14 or post-treatment clearance may predict favourable clinical outcomes, while secondary MET mutations and other acquired gene alterations may explain resistance to savolitinib. Registration: The trial was registered with ClinicalTrials.gov (NCT02897479) on 13 September 2016.